A produção de texto no curso de Letras : diagnóstico do ensinar a escrita - Ohuschi, Márcia Cristina Greco (2006)
The teaching of textual production in the training of the Portuguese Language teacher, at University level, and a diagnosis of the training that Language students receive during their studies at the State University of Maringá, Maringá PR Brazil, on the procedures in the teaching of writing are provided. The aim of current research is a discussion on text production studies at the University from the point of view of Applied Linguistics and within the social and interaction perspective, chiefly based on Bakhtin's and Vygotsky's theoretical presuppositions and on those by other Brazilian researchers and followers. Research intends to be a contribution towards the training of the Portuguese Language teacher in the context of teaching pedagogy within the Language and Literature Course. An ethnographical and applied qualitative and interpretative research will be presented throughout a follow-up of students reading the discipline Portuguese Language Teaching Practice at the State University of Maringá during 2004. The entire process within the practice of Text Production shall be analyzed. Since theoretical discussions on the theme, the working out of practical activities (monitored teaching included) and reflection diaries have been reported in note-books, the concept of writing was diagnosed. This specific discipline has been chosen since the students practice their knowledge, acquired through the university course, in real conditions of teaching in classes of the Primary and Secondary Schools. Results show that the process was not affected by linguistic theories, in particular those representing the social and interaction perspective, such as Bakhtin's and Vygotsky's. This is due to the fact that theoretical readings are outsourced and only re-readings were undertaken. Further, discussions and approaches on aspects of interaction and writing concepts are given rather superficially and in a fragmented manner. It has been detected that writing as a consequence is predominant in monitored teaching, even though certain students under analysis may be placed within an interface between this concept and the idea of writing as assignment. The difficulties experienced by the students in placing themselves as others have been perceived in the Diaries. They actually either fail to reflect on the several issues raised during the monitored lessons or they do so in a superficial ay. The curriculum of the Language and Literature Course at the State University of Maringá lacks the capacity for students to build a concept of writing consolidation throughout the undergraduate course. This is due to the fact that disciplines are compartimentized and the students do not read, discuss or study on any aspect of the theory of writing for two whole years. Such a gap affects the practice of would- be teachers in the classroom. Actually it has been verified that in their practical activities the students tried to introduce new ideas but failed to follow up the process. Since they revert to writing as a consequence, the fact reveals that the traditional teaching of text production is still deeply ingrained in their mind.